lncSAMM50 Enhances Adipogenic Differentiation of Buffalo Adipocytes With No Effect on Its Host Gene - Zhu, Ruirui; Feng, Xue; Wei, Yutong; Guo, Duo; Li, Jiaojiao; Liu, Qingyou; Jiang, Jianrong; Shi, Deshun; Huang, Jieping (Frontiers in Genetics, 2021)
Fat deposition is one of the most important traits mediated by a set of complex regulatory factors in meat animals. Several studies have revealed the significant role of lncRNAs in fat deposition, while the precise regulatory mechanism is still largely elusive. In this study, we investigated the lncRNA profiles of adipose and muscle tissues in buffalo by using the Illumina HiSeq 3000 platform. In total, 43,809 lncRNAs were finally identified based on a computer algorithm. A comparison analysis revealed 241 lncRNAs that are differentially expressed (DE) in adipose and muscle tissues. We focused on lncSAMM50, a DE lncRNA that is highly expressed in adipose tissue. Sequence alignment showed that lncSAMM50 is transcribed from the antisense strand of the upstream region of sorting and assembly machinery component 50 homolog (SAMM50), a gene involved in the function of mitochondria and was subsequently demonstrated to inhibit the adipogenic differentiation of 3T3-L1 adipocyte cells in this study. lncSAMM50 is highly expressed in adipose tissue and upregulated in mature adipocytes, and it mainly exists in the nucleus. Gain-of-function experiments demonstrated that lncSAMM50 promotes adipogenic differentiation by upregulating the expression of adipogenic markers but has no effect on its host gene, SAMM50, in buffalo adipocytes. These results indicate that lncSAMM50 enhances fat deposition in buffalo and provide a new factor for the regulatory network of adipogenesis.